1995
DOI: 10.1128/jb.177.8.1938-1946.1995
|View full text |Cite
|
Sign up to set email alerts
|

Tn916 target DNA sequences bind the C-terminal domain of integrase protein with different affinities that correlate with transposon insertion frequency

Abstract: The conjugative transposon Tn916 inserts with widely different frequencies into a variety of target sites with related nucleotide sequences. The binding of chimeric proteins, consisting of maltose-binding protein fused to Tn916 integrase, to three different target sequences for Tn916 was examined by DNase I protection experiments. The C-terminal DNA binding domain of the Tn916 integrase protein was shown to protect approximately 40 bp, spanning target sites in the orfA and cat genes of the plasmid pIP501 and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 47 publications
3
44
0
Order By: Relevance
“…Furthermore, in this work, we have shown that there is an extended consensus sequence in strain R20291 compared to that of 630, suggesting that there are differences between the two strains that influence target site selection by Tn916. This could be local variation in DNA topology, as it has been shown that Tn916 is likely to preferentially insert into targets that have a static bend (19).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in this work, we have shown that there is an extended consensus sequence in strain R20291 compared to that of 630, suggesting that there are differences between the two strains that influence target site selection by Tn916. This could be local variation in DNA topology, as it has been shown that Tn916 is likely to preferentially insert into targets that have a static bend (19).…”
Section: Discussionmentioning
confidence: 99%
“…The secondary structure of Int 6 may therefore result in an optimal interaction with integrase which would explain why Tn916 integration occurs here more frequently than at other target sites. The affinity with which a target site binds integrase and hence the frequency with which it experiences Tn92 6 insertion may therefore be dictated in part by its secondary structure (Lu & Churchwood, 1995).…”
Section: Although It Is Well Established That the Transposonmentioning
confidence: 99%
“…This observation may explain why Int 6 acts as a 'hot-spot' for Tn916 insertion. (Lu & Churchwood, 1995) were identified. These sites were not used by Tn916 in subsequent transformation experiments, indicating that it could integrate into the Rd genome at sites which did not fit the consensus sequence.…”
Section: Searching the H Influenzae Rd Genome Sequence With A Modifimentioning
confidence: 99%
See 2 more Smart Citations